Early Marriage Trends in The Perspective of Islamic Family Law: Between Regulation and Social Reality - Saini, Saini; Ulum, Bachrul (JURNAL ISLAM NUSANTARA, 2024)
This research is motivated by the high rate of early marriage in the Jember Regency, even though there are regulations that set a minimum age limit for marriage. This phenomenon is a serious concern considering the negative impacts it causes, both in terms of health, education, and social welfare. This study aims to explore the social and cultural factors that influence the practice of early marriage and evaluate the effectiveness of implementing regulations on the age limit for marriage in the region. This study uses a qualitative approach with a case study method, where data is collected through in-depth interviews, observations, and analysis of related documents. The study results show that although regulations have been implemented, their implementation is still hampered by the strong local culture that supports early marriage and low public awareness of the risks and implications of early marriage. In addition, socialization and supervision efforts from the government still need to be improved to be more effective. The discussion of this study highlights the need for a more holistic approach in dealing with early marriage by involving various parties, including religious and community leaders, to support more significant changes in community behavior towards early marriage.